Indonesian EFL students’ voice on the first language usage in classroom - Binti Muifatun Nazilah; Peptia Asrining Tyas; Wiwik Umiyati (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2021)
The first language (L1) usage is still found during the English lesson, specifically in non-native English countries. This may be a debatable issue among experts. Hence, investigation on students’ perception is helpful in this study. It will give an insight into students’ preferences for learning the language. The previous studies related to this topic were mainly focused on senior high school and undergraduate students as the subject. Therefore, this present study proposed to explore the perception of junior high school students. In conducting this study, the researcher applied a quantitative survey design. There were 29 questions in three sections that were distributed to investigate: (1) the language used in the EFL classroom, (2) students’ attitudes as well as (3) students’ well-being during the English foreign language lesson. The participants were 101 students of SMP Shalahuddin Malang. The findings revealed that students have positive responses towards the use of Indonesian languge during the EFL lesson.   DOI: 10.26905/enjourme.v6i2.6701